PENGARUH KARAKTERISTIK PETANI, MOTIVASI PETANI DAN PERAN PENDAMPING TERHADAP PERILAKU PETANI PENANGKAR DALAM MENDUKUNG KETERSEDIAAN BENIH PADI DI KABUPATEN TABANAN - Purwanta, I Putu Adi; Oka Suardi, I Dewa Putu; Surya Diarta, I Ketut (JURNAL MANAJEMEN AGRIBISNIS (Journal Of Agribusiness Management), 2019)
Seed is essential support farming success. Availability it required support agricultural development. The purpose this study to analyze direct and indirect effects farmers characteristics, motivation and role of assistant on the behavior breeder farmers and their influence on the availability rice seeds. The study conducted in Tabanan Regency. Data collection done from March to June 2019.  The number of population 142 rice breeders with respondent 59 rice breeders. The number of respondents determined using  Slovin formula. Analysis tool used SmartPLS version 3.0. The results of study showed farmers characteristics, motivation, and role of assistant had a significant effect on the behavior  breeder farmers. Moreover, seed availability was affected by role of assistant, yet farmers characteristics and motivation had no notable effect on it. However, the indirect influence farmers characteristics, motivation and role of assistant not significant to seed availability through the behavior breeder farmers. From this study, it’s suggested that 1) to maintain availability rice seeds in Tabanan Regency, role of assistant for farmers cultivate in own fields is optimized according to their respective duties and functions. 2) Role of assistant are role subak, PPL, BPSBTPH, breeders, and the local agriculture office 3) To improve the financial ability local breeders to buy prospective seeds produced by breeder farmers.